Executives' Legal Expertise and Corporate Innovation - Dai, Yunhao; Tong, Xinchu; Jia, Xiao (Corporate governance : an international review, 2024)
ABSTRACT Research Question This study investigates whether and how executives with legal expertise impact corporate innovation. Research Findings Using a sample of listed firms in China, we have the following findings: (1) Firms that hire executives with legal expertise are associated with more corporate innovation. (2) These firms talk about potential legal risks and legal advisors more often in their annual reports and have lower chances of being sued in patent litigations. (3) The innovation‐promoting effect is stronger when the firms are state‐owned enterprises, have more overseas revenue, operate in high‐tech industries, have prior patent litigation experience, and are in strong legal environments. Theoretical/Academic Implications The findings indicate that executives with legal expertise bring more attention to legal risks and help the firm to shape a stable environment, which can effectively promote innovation activities. Also, the innovation‐promoting effect of lawyer executives complements the role of in‐house legal counsels and the external legal environment. This paper adds to the literature on the value of executives with legal background. Practitioner/Policy Implications Our results emphasize the important role played by executives with legal expertise in corporate innovation. Given the continuing shortage of legal talents and the gradual improvement of the legal system in China, firms need to employ more legal talents to avoid potential legal risks and maintain sustainable growth.